Development Strategy for Islamic Boarding School / Dayah Maqamam Mahmuda Takengon - Emy Yusdiana; Ihsan Harun (Budapest International Research and Critics University, 2022)
Islamic Education Institutions, as an inseparable sub part of the social life system of society, nation and state, absolutely have awareness of their environment. They must realize that the existence of the elements around them can help or hinder their survival. Therefore, it is important to study the strategic activities of the Pesantren/Dyah Maqamamam Mahmuda development strategy in the hope of continuing to strive to maintain or develop the organization. Through a literature review, this article attempts to analyze the environmental elements of the Maqamam Mahmuda Islamic Boarding School/Dayah, both internally and externally. It is hoped that the results of the study will provide a perspective for the manager of the Maqamam Mahmuda Islamic Boarding School/Dayah regarding the urgency of the analysis